Comparative evaluation of magnetic resonance arthrogram with arthroscopy in knee pathologies - Harish Deepak P,; Prem Chand Paladugu,; James, Boblee (Asian Journal of Medical Sciences, 2023)
Background: Magnetic resonance arthrogram (MRA) has emerged as a supplement to non-contrast magnetic resonance imaging (MRI), especially in the identification of meniscal and chondral pathologies. It has increased the diagnostic efficacy of MRI in the evaluation of knee pathologies. Aims and Objectives: The present study was carried out to evaluate the role of MRA in the diagnosis of various knee pathologies and to correlate its findings with arthroscopy. Materials and Methods: A total of 56 patients with knee pain scheduled to undergo arthroscopic evaluation were enrolled in the study and were assessed using MRA before arthroscopy. MRA findings were correlated with arthroscopic findings. The level of agreement was measured using kappa statistics. Diagnostic efficacy was assessed in terms of sensitivity, specificity, positive predictive value, and negative predictive value. Results: Cartilage involvement (48.2%), anterior cruciate ligament (ACL) tear and medial meniscus tear (37.5% each), bony injury (n=12; 21.4%), chondral defect (n=11; 19.6%), posterior cruciate ligament tear (n=10; 17.9%), and lateral meniscus tear (n=8; 14.3%) were the knee pathologies confirmed by arthroscopy. MRA had a sensitivity and specificity of 100% for pathologies such as ACL tear, lateral meniscus tear, medial meniscus tear, and bony injury. It was 100% specific for all the pathologies with no false positive detection. There was a strong to perfect agreement between MRA and arthroscopic findings for different knee pathologies. Conclusion: The present study found MRA to be a highly specific diagnostic tool for the diagnosis of different knee pathologies and it is useful in reducing the burden of undesired invasive arthroscopies.